2014
DOI: 10.1007/s00167-014-2877-9
|View full text |Cite
|
Sign up to set email alerts
|

No clinical difference between fixed- and mobile-bearing cruciate-retaining total knee arthroplasty: a prospective randomized study

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
6
26
0
Order By: Relevance
“…The x-axis values of 1 to 10 correspond to the interval years (zero to one through nine to ten years). The graphs depict the fixed-effects model, results of which are also shown in Table II Different results have been reported for mobile-bearing total knee arthroplasty implants [22][23][24][25] . A well-conducted prospective, randomized trial did not show any significant differences between mobile-bearing and fixed-bearing total knee arthroplasty regarding function but was not large enough to look at revision occurrence 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The x-axis values of 1 to 10 correspond to the interval years (zero to one through nine to ten years). The graphs depict the fixed-effects model, results of which are also shown in Table II Different results have been reported for mobile-bearing total knee arthroplasty implants [22][23][24][25] . A well-conducted prospective, randomized trial did not show any significant differences between mobile-bearing and fixed-bearing total knee arthroplasty regarding function but was not large enough to look at revision occurrence 6 .…”
Section: Discussionmentioning
confidence: 99%
“…53 However, there were no differences in survival and clinical outcomes between mobile-bearing and fixed-bearing prostheses at short-and midterm follow-up. 54,55 More data are necessary to address questions related to long-term wear or late revisions. The high survivability and clinical success attained with the CR implants has contributed to the increasing popularity of TKA.…”
Section: Posterior Cruciate-retaining Implantsmentioning
confidence: 99%
“…While some reports show less anterior knee pain with rotating platforms, 29,30 most studies have not found an improvement in pain or function. 3,[31][32][33][34][35][36][37][38][39] Similarly, our institution has performed several studies, 1,[40][41][42] all of which have failed to find any advantage of rotating platforms. Although, most metaanalyses 31,43,44 confirm that there is no difference in pain, motion, or function; one recent meta-analysis 45 did report a lesser incidence of pain with rotating platforms.…”
Section: Clinical Outcomesmentioning
confidence: 99%